The contagion effect: Evidences from former Soviet economies in eastern Europe - (:unkn) unknown (My University, 2010)
This paper analyzes the existence of contagion effect among the seven former- Soviet economies in Eastern Europe: Belarus, Estonia, Latvia, Lithuania, Moldova, Russia and Ukraine throughout the period from November 1995 to December 2009. Additionally, the economies and the sample period employed in this research give an opportunity to test for two hypotheses on the contagion effect: First, the "flight to quality" hypothesis suggested by Favero and Giavazzi (2002) and second, the "political contagion" hypothesis offered by Drazen (1999). The contagion effect hypotheses for each economy have been tested using the "Threshold Test" proposed by Pesaran and Pick (2007). Empirical analysis has highlighted the existence of contagion effect in the region and supported the validity of "flight to quality" hypothesis. The results are consistent with the different regional patterns of the former Soviet countries. © EuroJournals Publishing, Inc. 2010.
Keywords: Contagion; Eastern europe; Flight to quality; Political contagion; Threshold test